Evidence on Contagion in Earnings Management - Kedia, Simi; Koh, Kevin; Rajgopal, Shivaram (The Accounting Review, 2015)
ABSTRACT We examine contagion in earnings management using 2,376 restatements announced during the years 1997–2008. Controlling for industry and firm characteristics, firms are more likely to begin managing earnings after the public announcement of a restatement by another firm in their industry or neighborhood. Such contagion is absent when the restating firm is disciplined by the SEC or class action lawsuits, suggesting deterrent effects of enforcement activity. Contagion among peers is observed (1) in the same account as the one restated by the target firm, or (2) when larger target firms restate or the restatement is prominently disclosed, or (3) when the target firm's restatement is less severe. Contagion stops during the years 2003–2005, possibly due to the enforcement associated with the Sarbanes-Oxley Act (SOX), but reappears during 2006–2008, perhaps because the sting associated with SOX has worn off. In sum, peers' actions appear to affect a firm's earnings management decisions.